PENILAIAN KONDISI DEGRADASI TANAH DI SPK SAWANGAN KOTA DEPOK - Irman Firmansyah; Tatan Sukwika (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2020)
The establishment of Sawangan district, Depok municipality as an urban service sub-centres (SPK) has encouraged urbanization to the zoning. The population increase and the demand for land for the conversion is a consequence. Land-use change has become an environmental issue in the SPK Sawangan, specifically soil degradation. The objectives of this study were to assess the condition of soil degradation based on the criteria for evaluating the parameters of soil physical properties in the SPK Sawangan. Observation method on the soil physical properties were carried out at five sample plots. The assessment technique referred to standard assessment criteria for controlling soil degradation for biomass production. The results showed that the parameters that affect soil degradation are acidity (T1,T3, T5), soil bulk density (T4), permeability: fast (T2,T3) and slow (T4). Overall conclusions, soil degradation at the SPK Sawangan zoning shows the condition of low damage. The policy implications are that stakeholders need to carry out technical management of land, especially on land that has the limiting parameter value that exceeds or is outside the critical threshold value.